Experimental Dataset on Eye-tracking Activity During Self-Regulated Learning - Vojtěch Juřík; Libor Juhaňák; Alexandra Ružičková; Nicol Dostálová; Zuzana Juříková (Scientific Data)
Abstract The cognitive processing of learning materials has been extensively studied within various cognitive theories. Self-regulated learning (SRL) is also recognized as a key factor in learning efficiency. However, evidence linking SRL to learning outcomes remains inconclusive, particularly regarding objective behavioral data during learning. This study presents an original empirical dataset on eye-tracking activity during learning, examining the effects of metacognitive prompts and multimedia content on cognitive processing and learning outcomes. A controlled laboratory experiment with a 2 × 2 mixed factorial design involved 110 university students, resulting in 84 complete recordings of eye-movement activity during learning. Participants studied scientific materials in text-only and multimedia formats, with one group receiving metacognitive prompts and the control group receiving general instructions. Learning performance was assessed via a post-test, and eye-tracking technology captured gaze patterns to provide insights into cognitive engagement and attention distribution. Applications extend to e-learning, virtual environments, and user interface design. While the dataset has some methodological limitations, it remains a robust resource for studying cognitive processes and optimizing educational technologies.